The Problem of Oil Traffic in the Black Sea Straits and the Prospects of the “Bourgas-Alexandroupolis Project”. - Ioannis Mazis (Defensor Pacis, 2005)
The recent activity of the events over the project has been handled by the experts with restraint. The negotiations between the Russian President Putin and the Greek Prime Minister Mr. Karamanlis that took place in Moscow in December 2004 did not make the situation over the future of the project any clearer. We cannot deny that among many Bosporus bypassing projects, it is the Bourgas-Alexandroupolis project that is the most advantageous for Russia from the geopolitical point of view. And it is logical to assume that the Russian authorities will be guided by the geopolitical interests of the country, while making a decision on overcoming the Bosporus deadlock. The same interests will no doubt become the decisive ones for the policy of the oil companies that are likely to participate in the project. In any case, we should take into account that Russian oil exports are almost completely controlled by the government, and the decision on choosing new export routes is its exclusive prerogative. Thus, the “last word” on the future of Bourgas-Alexandroupolis will be said by the Russian president. The project could be also promoted by the European Union, and it will be in line with the economic and political interests of the EU, that in the future it can confront the situation when Turkey will control oil traffic from the Caspian region to Europe. However, until now there has not been any essential reaction from the EU authorities, and the European Committee on Transport, Energy and Communications has concentrated its attention on the disputable Ukrainian route Odessa-Brody.